Species richness of trees in disturbed habitats within a protected area and its implications for conservation: The case of Mt. Apo Natural Park, Mindanao Island, Philippines - BENEDICT R. ZAPANTA; MARION JOHN MICHAEL M. ACHONDO; AARON FROILAN M. RAGANAS; FRITZIE A.; AILEEN GRACE D. DELIMA; JUNALDO A. MANTIQUILLA; ROBERTO P., JR. PUENTESPINA; FLORENCE ROY P. Salvaña (Society for Indonesian Biodiversity, 2019)
Abstract. Zapanta BR, Achondo MJMM, Raganas AFM, Camino FA, Delima, AGD, Mantiquilla JA, Puentespina, RP, Salvaña FRP. 2019. Species richness of trees in disturbed habitats within a protected area and its implications for conservation: The case of Mt. Apo Natural Park, Mindanao Island, Philippines. Biodiversitas 20: 2081-2091. In order to improve forest management, it is fundamental to develop baseline information on species distribution i.e., richness and presence of endemic and threatened species in varying conditions of environmental degradation. In the Philippines, there is a growing number of studies which provided important information on pristine habitats (e.g. primary forest), however, there is a scarcity of studies on disturbed habitats. Here, we present baseline information on the tree species diversity in disturbed habitats like those portions converted to agricultural lands planted with fruit trees and other commercial crops within Mt. Apo National Park. A total of 139 tree species including a single gymnosperm was identified within the study sites. Of the species identified, the dominant families included Moraceae, Euphorbiaceae, Fabaceae, Meliaceae, Lauraceae, Myrtaceae, Arecaceae, Dipterocarpaceae, and Verbenaceae. Nineteen species were considered endemic including the Mindanao endemic, Lindera apoensis. Within this number, 47% are considered threatened on their range and four species viz. Parashorea malaanonan, Shorea contorta, and Shorea negrosensis are Critically Endangered with decreasing population records. The results of this current study suggest that disturbed habitats in Mt. Apo Natural Park still harbor endemic and threatened species, which are ecologically and economically important. Establishing a list of tree species in the area provides important information needed for the restoration of some disturbed areas which are abandoned by locals. The presence of endemic and threatened species also indicates that conservation, protection, and forest management efforts should be extended and allocated towards disturbed areas in the national park.